The Impact of Media Exposure on the Poetry Writing Skills of Class X Stu-dents: Exploring the Role of the Connecting Motif - Ellison, Dwivedi; Callista, Meiyanti (Insan Akademika Publications, 2024)
In a digital age where media consumption is ubiquitous, understanding the impact of media exposure on the creative abilities of students is imperative. This research explores the intricate relationship between media exposure and the poetry writing skills of Class X students, focusing on the thematic motif of